ANALISIS BALIK LERENG LOWWALL PADA “BLOK X” KABUPATEN TANAH BUMBU, PROVINSI KALIMANTAN SELATAN: BACK ANALYSIS OF LOWWALL SLOPES IN "BLOCK X" DISTRICT TANAH BUMBU, SOUTH KALIMANTAN PROVINCE - Putri, Al Zahra; Imam Setiaji Ronoatmojo; Wijaya, Budi (Journal of Geoscience Engineering and Energy, 2024)
Coal mining companies usually apply the open pit mining method in carrying out coal mining. Mining activities always have risks that cannot be avoided and unpredictable, one of which is a landslide in the mining area. Therefore, it is very necessary to control the risks of mining activities. One of them is like designing a slope design in the mine which is included in geotechnical aspects. And in the geotechnical aspect, it has a reverse analysis method that is very useful to determine the cause of avalanches in the area.